1989
DOI: 10.1007/bf00319593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous light on rat parotid gland structure and reactivity

Abstract: The effects of continuous light on ultrastructural organization and sympathetic secretory responses of the rat parotid gland are reported. After 50 days of continuous light exposure, the fine structure of the parotid gland exhibited features of enhanced secretory activity as judged by the striking development of rough endoplasmic reticulum and Golgi complexes, the depletion of secretory granules and the increased turnover of secretory cells. The secretory responses of parotid gland to isoproterenol revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In our previous study the loss of cell polarity accompanying the disruption of the acinar configuration ruled against optimal localization of a fluorescent signal to a specific cytoplasmic component of dispersed parotid cells [5]. In intact acini the basal pole expressed the highest levels of RyRs, where the ER is most concentrated [18,21], and the expression of receptors decreased through the apical pole where the ER is sparsely expressed, thus suggesting the ER as the locus of RyR expression. RyR expression has also been detected by immunofluorescence in the submandibular (salivary) gland, but in contrast with our findings its localization was confined to the luminal pole and basolateral membrane [22].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous study the loss of cell polarity accompanying the disruption of the acinar configuration ruled against optimal localization of a fluorescent signal to a specific cytoplasmic component of dispersed parotid cells [5]. In intact acini the basal pole expressed the highest levels of RyRs, where the ER is most concentrated [18,21], and the expression of receptors decreased through the apical pole where the ER is sparsely expressed, thus suggesting the ER as the locus of RyR expression. RyR expression has also been detected by immunofluorescence in the submandibular (salivary) gland, but in contrast with our findings its localization was confined to the luminal pole and basolateral membrane [22].…”
Section: Discussionmentioning
confidence: 93%
“…The three InsP $ R subtypes previously detected in exocrine pancreas and submandibular (salivary) glands were likewise localized in proximity to the apical (luminal) membrane [22,29]. Because Ins(1,4,5)P $ -sensitive Ca# + release is closely linked to the ER [30], the immunofluorescence data that identify the apical pole as a major site of the InsP $ R and therefore a primary locus of Ca# + signalling must be reconciled with morphological data revealing that apical ER is sparsely expressed in the resting parotid cell [18,21]. Whereas Ca# + -containing zymogen granules predominate in the apical pole, they do not appear to be responsible for any major contribution to Ca# + signalling in exocrine acinar cells, including parotid cells [29,31].…”
mentioning
confidence: 99%
“…In this respect, it is known that chemical-induced sympathectomy prevents fructose secretion in prostate and seminal vesicle of rats (Lamano et al, 1990). Moreover, previous works in our laboratory have shown that chronic exposure of rats to constant light promotes an alteration in sympathetic parotid and submaxillary glands secretory response (Chiarenza et al, 1989;Gallará and Bellavía, 1995). Whatever the effect of continuous lighting on the secretory activity of the epididymis it remains to be elucidated.…”
Section: Discussionmentioning
confidence: 90%
“…It was assumed that chronic exposure to constant light would increase the adrenergic changes usually produced by the light stimuli. In comparison to parotid gland from rats under a normal photoperiod, a 50% reduction in acinar cells rich in secretion granules was seen in glands from rats after 50 days of continuous light exposure (57). An increase in adrenergic responses was assumed, because in the rat parotid glands there is a clear correlation between cellular degranulation and sympathetic nerve activity (58).…”
Section: Chromic Exposure Of Rats To Constant Light • Effect On Ultramentioning
confidence: 99%